Wellington's Victory arranged for string quintet - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Austria; S. A. Steiner; Vienna, 2023)
Arrangement for string quintet of Wellington's Victory (Wellingtons Sieg), originally published for orchestra; first edition, later issue from after 1820, lacking the subscription announcement on the first page of the violin 1 part.